Spatial stratification of each spatial domain cluster elucidating endothelial cell invasion into the tumor. - Shunsuke A. Sakai (13789939) (2025)
(A) Spatial distributions of stratified spatial domain clusters into (−30, 0], (0, +30], and (+30, +60] sections. (B) Violin plots showing the endothelial cell marker gene expressions (PECAM1, VWF, and CD93) for each cluster in the (−30, 0], (0, +30], and (+30, +60] sections. The x-axes indicate cluster numbers, and the y-axes indicate scaled gene expression levels. The annotated values are the P values of the significance test. (C) Representative images of DAPI with epithelial cell markers (CDH1 and EPCAM) and endothelial cell marker (CD93, PECAM1, and VWF) expression for four ROIs.